Agro‐morphological Characterization of West and Central African Pearl Millet Accessions. Issue 2 (1st March 2015) - Pucher, Anna; Sy, Ousmane; Angarawai, Ignatius I.; Gondah, Jada; Zangre, Roger; Ouedraogo, Mahamadi; Sanogo, Moussa D.; Boureima, S.; Hash, C. Tom; Haussmann, Bettina I.G.
ABSTRACT: Pearl millet [ Pennisetum glaucum (L.) R. Br.] was domesticated in Sahelian West Africa. This highly outcrossing crop is one of the most important staple cereals in the semiarid tropics, adapted to very harsh rain‐fed conditions. Agro‐morphological characterization of local germplasm is very important to better understand existing diversity, ease targeted genetic broadening of breeding populations, and potentially link this knowledge to genotypic information. The objectives of our study were to (i) characterize West and Central African (WCA) pearl millet accessions based on their agro‐morphological traits; (ii) evaluate the possibility to group accessions based on their agro‐morphological characteristics; (iii) determine geographic patterns of phenotypic differentiation; and (iv) derive conclusions for pearl millet improvement in WCA. A total of 360 early‐to‐medium maturity accessions were phenotyped for 12 agro‐morphological traits at six environments in WCA. Wide ranges of all observed traits indicated a high diversity of the tested accessions. Principal component analysis revealed very large diversity within individual countries, especially within Mali and Burkina Faso. Some limited grouping of accessions from Niger, Senegal, Cameroon, Morocco, and Mauritania was observed for individual principal component axes. Geographical differentiation and country differences were detected for several traits. The results and data presented in our study reflect WCA pearl millets' tremendous diversity and adaptability to a wide range of environments and give a sound basis for breeders to select and utilize this germplasm to serve the manifold needs of WCA pearl millet farmers.